Use of Xpert MTB/RIF Ultra assays among paediatric tuberculosis experts in Europe. Issue 5 (17th May 2018) - Villanueva, Paola; Neth, Olaf; Ritz, Nicole; Tebruegge, Marc
We read with interest the recent editorial by Cabibbe et al . [1], which highlights the importance of rapid molecular tuberculosis (TB) assays for patient care. Only few paediatric TB experts based in Europe had access to the Xpert MTB/RIF Ultra assay, a new generation molecular TB test, by the end of 2017 http://ow.ly/ZgoF30jHShY